PENGGUNAAN METODE DISKUSI UNTUK MENINGKATKAN HASIL BELAJAR ILMU PENGETAHUAN SOSIAL DI KELAS IV - Herlina, Sunya; Marli, Suhardi; Salimi, Asmayani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
This research aimed to increase students’s learning result of social science in grade IV SDN 03 Tamong Bengkayang. The research’s method used was descriptive with classroom action research type. There are four steps of research procedure. Those are planning, action, observation and reflection. This research has done on 3 cycles. Data resources were teacher and students of grade IV SDN 03 Tamong Bengkayang. The result of this research showed that the ability of teacher to arrange learning draft from cycle I was 2,88, in cycle II was 3,72 and became 3,80 in cycle III. The ability of teacher to do learning showed increase from cycle I 2,92, in cycle II was 3,65 and became 3,72 in cycle III. Students learning outcome increased from cycle I with score 35,34, 40,67 in cycle II and increased 66,92 in cycle III. The using of discuss method increased the result of social science students learning outcome.Keywords : discuss method, learning outcome, social science